Pengaruh Tingkat Pengetahuan Dan Sikap Terhadap Perilaku Penanganan Sanitasi Lingkungan Masyarakat Di Kota Palu - Miswan, Miswan; Rasyid, Rusman (Pascasarjana Universitas Negeri Makassar, 2020)
Sanitation as one of the aspects of development has an important function in supporting the level of people's welfare because it is related to health, lifestyle, residential environment conditions, aesthetics and comfort in everyday life. Sanitation is one of the most important factors in realizing services related to poverty alleviation and increased productivity. This study aims to determine the effect of knowledge and attitudes in handling environmental sanitation. The design of this study is based on the SEM model, assuming that all variables are considered to have direct or indirect influence. This type of research is a quantitative study through the survey research phase. In the survey, research was not carried out on all objects studied or population, but only took part of the population (sample) of the community, namely to describe the influence of knowledge and attitudes in handling environmental sanitation. The results of the study show that the knowledge environment variable has a direct or indirect influence on the variable behavior of the community in handling environmental sanitation. While the indirect influence of this variable is through the influence on attitudes in managing the environment.